Analisis Peran Visual Media Cetak Dalam Meningkatkan Minat Konsumsi Sayuran pada Anak - Vega, Nadia (Fakultas Desain Universitas Komputer Indonesia, 2024)
Children's interest in consuming vegetables is still quite low, even though a lack of vegetable intake can increase the risk of health problems and nutritional deficiencies in the body, especially for children who are still growing. Therefore, there is a need for media that can encourage children's interest in consuming vegetables. This research aims to analyze how visual media can play a role in increasing vegetable consumption among 3-7-year-olds by using print media in the form of flashcards, quiet books/busy books, and board books with vegetable themes. Data collection methods will be taken from various existing studies on the three print media that have been selected and several questions to see children's responses to visuals in print media. It is hoped that this research can help identify which media are most effective in getting children interested in vegetables.